PENGARUH MEDIA PEMBELAJARAN FISIKA BERBANTUAN APLIKASI CANVA TERHADAP MINAT BELAJAR - Wa Sarnia Binongko; Salwa Rufaida; Tri Hastiti Fiskawarni (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2024)
This research aims to determine the effect of physics learning media assisted by the Canva application on interest in learning. The type of research used is quasi-experimental, with a nonequivalent control group design. The population is all students in class XI Science, with samples taken from class XI IPA 1 and class Based on the pretest results that have been analyzed, the average score is 87.8 for the experimental class, while in the control class the average score is 87.1. This shows that the initial abilities in both classes are almost the same. Based on the posttest results that have been analyzed, it can be seen that there was an increase in interest in learning in physics subjects after being given treatment in the form of learning media assisted by the Canva application in the experimental class, which can be seen in the average score of 119.0, whereas in the control class which only used media. conventional power points obtained an average score of 107.9. So it can be concluded that interactive learning media such as Canva has an influence on interest in learning. Because by using Canva as a learning media that is interesting and relevant to students' daily lives, it can trigger curiosity with various kinds of critical questions which then motivate students to get involved in the physics learning process, so that they can increase interest in learning physics learners. Keywords: Physics, Canva Learning Media and Interest in Learning.